Impact of Wave Number Choice in Spectral Nudging Applications During a South Atlantic Convergence Zone Event - Silva, Natália Pillar da; Camargo, Ricardo de (Frontiers in Earth Science, 2018)
Several studies showed the advantages of using nudging techniques to enforce the evolution of a numerical model to approximate large-scale features to a reference. Spectral nudging applications are particularly useful since they also provide the ability to maintain higher temporal and spatial variability in the simulations results. In this study, different nudging configurations are tested for an intense South Atlantic Convergence Zone (SACZ) event. Large-scale features directly modulate the SACZ formation and persistence. Therefore, the employment of relaxation methods enhances the representation of continental-wide features from lateral boundary conditions over the interior of broad domains. Results show that Spectral Nudging is very effective at imposing the selected synoptic scales onto the solution, while allowing the limited-area model to incorporate finer-scale features. Wave numbers with associated length scales of 2000km are ideal to enforce large-scale fields to represent features important for the SACZ formation and persistence. Using larger wave numbers can improve the simulation performance, but at a cost of damping the model dynamic and physical contribution to the final solution.